Faktor-Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Manufaktur - Henny, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to obtain empirical evidence regarding leverage, liquidity, total asset turnover, and firm size on profitability. The sampling technique used in this study was purposive sampling with the data used was pooled data. The research sample used was 62 manufacturing companies listed on Indonesia Stock Exchange (IDX) in the period 2014-2017. The results of the research with testing the hypothesis by using the t statistical test show that leverage and liquidity did not have a significant effect on profitability, while the total asset turnover and firm size have a significant positive effect on profitability.